The Effect of Principal Leadership, Pedagogic Competence, and Work Motivation on the Performance of Madrasah Tsanawiyah (MTs) Teachers in Purworejo Regency - Sumidah Sumidah (LPPM IAINU Kebumen, 2019)
This research is based on the problem of unsatisfactory teacher performance.In connection with this, this study aims to determine the effect principal leadership, pedagogic competence, and work motivation on performance Madrasah Tsanawiyah (MTs) teachers in Purworejo District. This research is correlational quantitative research. The population in this study were all teachers MTs in Purworejo Regency, while the research sample is the teacher of MTs N 1 Purworejo: 44 people, teachers at MTs An Nawawi Berjan Purworejo: 40 people, and teachers at MTs Al Iman Bulus Purworejo: 58 people. Data collection using a questionnaire, and data analysis using simple regression analysis techniques and multiple regression. This research produces conclusion as follows. (1) Principal leadership has a positive influence andsignificantly to the performance of MTs teachers in Purworejo Regency, as evidenced by the value Sig = 0.00 < α = 0.05. The value of tcount = 9.262, p = 0.000, and the correlation coefficient (r2) = 0.380 or contribute by 38.0%. (2) Pedagogic competence has a positive and significant effect on The performance of MTs teachers in Purworejo Regency is evident from the Sig = 0.00 < α = 0.05. As for value tcount = 11.490, p = 0.000, and the correlation coefficient (r2) = 0.485 or a contribution of 48.5%. (3) Work Motivation has a positive and significant effect on MTs Teacher Performance in Purworejo Regency, as evidenced by the value of Sig = 0.00 < α = 0.05. The value of tcount = 10.622, p = 0.000, and the correlation coefficient (r2) = 0.446 or a contribution of 44.6%. (4) Leadership Principals, Pedagogic Competence, and Work Motivation together have an influence positive and significant impact on MTs Teacher Performance in Purworejo Regency, as evidenced by the scores Sig = 0.00 < α = 0.05. The value of Fcount = 58.621, p = 0.000, and the correlation coefficient (R2) = 0.560or contribute 56.0%